The Clinical Relevance of Interdisciplinary Research on Affect Regulation in the Analytic Relationship - Altimir, Carolina; Jiménez, Juan Pablo (Frontiers in Psychology, 2021)
After more than a century of existence, theoretical development, research, and clinical practice within the psychoanalytic movement have consistently demonstrated that psychoanalysis is not a unitary and autonomous discipline. This has been evidenced by the various ways in which psychoanalytic thought and practice have been informed by and have established a dialogue – more or less fruitful – with related disciplines (neurosciences, developmental psychology, psychotherapy research, attachment theory and research, feminism, philosophy). This dialogue has contributed to a better understanding of the functioning of the human psyche, and therefore of the analytic process, informing clinical interventions. In turn, it has enriched research on psychoanalytic practice and process, underlining the fact that research in psychoanalysis is fundamentally about clinical practice. Since its origins, psychoanalysis has made explicit the work on the patient-analyst relationship as the terrain in which the analytic process unfolds. For its part, research in psychotherapy has demonstrated the relevance of the therapeutic relationship for the good development and outcome of any psychotherapeutic process. This supports the argument that research in clinical psychoanalysis should be research on the impact of the analyst interventions on the analyst-patient relationship. In this context, a central element of what happens in the analytic relationship refers to affect communication and therefore, affect regulation, which is manifested in the transferential and counter-transferential processes, as well as in the therapeutic bond. On the other hand, affective regulation is found at the crossroads of etiopathogenesis, complex personality models and psychopathology, allowing the understanding of human functioning and the staging of these configurations in the patient-analyst relationship. In this way, research on affective regulation in the analytic process is proposed as a path that exemplifies interdisciplinary research and scientific pluralism from which psychoanalysis enriches and progresses as a discipline. The case of a line of research on affective regulation in psychoanalytic psychotherapy is illustrated. The need to resort to other disciplines, as well as the translational value of our research and its clinical usefulness, is discussed.